AKSELERASI PENGELOLAAN LAPORAN KEUANGAN BUM DESA JAWA TIMUR - Nurhidayati Nurhidayati; Akhmad Priharjanto; Imam Subroto; Sandhyakalaning Jiwatami Ridwan Putri (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2025)
To strengthen financial governance in BUM Desa (Village Enterprises), the State Finance Polytechnic (PKN STAN), in collaboration with the Provincial Office of Community and Village Empowerment (DPMD) of East Java, implemented a community service program aimed at accelerating financial reporting capacity for BUM Desa. The program was carried out in three stages: (1) identification and profiling of BUM Desa practitioners, (2) capacity building through training and hands-on assistance based on the Financial Reporting Guidelines for BUM Desa (Ministerial Decree No. 136/2022) and an Excel-based accounting application, and (3) capacity strengthening through a Training of Trainers (ToT) scheme and a community of practice. The results show significant improvements in participants’ understanding of basic accounting, their ability to prepare financial statements, and the consistent application of accounting standards. The program also enhanced transparency and accountability in BUM Desa financial management. Challenges such as varying participant backgrounds, limited time availability, and technology-related constraints were addressed through practical learning approaches, intensive mentoring, and technical adjustments. Overall, this program contributes to the acceleration of creating auditable, transparent, and professionally managed BUM Desa that support sustainable rural economic development.Keywords: accounting, financial statement, human development